di STUDI PENYEBARAN KASUS PMK DI PULAU JAWA MENGGUNAKAN GEOGRAPHICALLY WEIGHTED NEGATIVE BINOMIAL REGRESSION - SUNARTA, NI MADE DEVIANI PRISILIA; SUCIPTAWATI, NI LUH PUTU; DWIPAYANA, I MADE EKA; SRINADI, I GUSTI AYU MADE; KENCANA, I PUTU EKA N.; JAYANEGARA, KETUT (E-Jurnal Matematika, 2025)
Foot and mouth disease (FMD) is a highly contagious disease that spreads rapidly and infects cloven-hoofed animals. The disease has become endemic in many countries, causing serious problems for the economy and livestock industry. Java Island has a high number of FMD cases with the number of cases showing variations caused by differences in geographical characteristics in each region and this cause spatial heterogeneity. Therefore, PMK case modeling was carried out to determine the factors that influence it using the Geographically Weighted Negative Binomial Regression (GWNBR) method where the FMD case data is count data and has overdispersion. Based on the results of the GWNBR model, there are five groups of districts/cities based on the predictor variables that have a significant effect on the spread of FMD with the dominant predictor variables that have a significant effect are livestock density, livestock population, and number of livestock conditionally slaughtered.